Students as Subjects in Behavioral Business Research. - Copeland, Ronald M.; Francia, Arthur J.; Strawser, Robert H. (The Accounting Review, 1973)
The article discusses a study on the measurement of the attitudes of students towards selected financial reporting practices. Results indicated that students are more familiar with concepts such as generally accepted accounting principles, comparability, consistency and uniformity. This is because of the students' academic preparation and exposure to the professional literature. However, the findings of the study raised doubt with regard to the effectiveness of the use of students as surrogates for businessmen in research.